Evolutionary descent of a human chromosome 6 neocentromere: A jump back to 17 million years ago - Capozzi, Oronzo; Purgato, Stefania; D'Addabbo, Pietro; Archidiacono, Nicoletta; Battaglia, Paola; Baroncini, Anna; Capucci, Antonella; Stanyon, Roscoe; Della Valle, Giuliano; Rocchi, Mariano (Genome Research, 2009)
Molecular cytogenetics provides a visual, pictorial record of the tree of life, and in this respect the fusion origin of human chromosome 2 is a well-known paradigmatic example. Here we report on a variant chromosome 6 in which the centromere jumped to 6p22.1. ChIP-chip experiments with antibodies against the centromeric proteins CENP-A and CENP-C exactly defined the neocentromere as lying at chr6:26,407–26,491 kb. We investigated in detail the evolutionary history of chromosome 6 in primates and found that the primate ancestor had a homologous chromosome with the same marker order, but with the centromere located at 6p22.1. Sometime between 17 and 23 million years ago (Mya), in the common ancestor of humans and apes, the centromere of chromosome 6 moved from 6p22.1 to its current location. The neocentromere we discovered, consequently, has jumped back to the ancestral position, where a latent centromere-forming potentiality persisted for at least 17 Myr. Because all living organisms form a tree of life, as first conceived by Darwin, evolutionary perspectives can provide compelling underlying explicative grounds for contemporary genomic phenomena.